Kesehatan Mental di Era Media Sosial : Perbandingan Hermeneutik Fazlur Rahman, Nasr Hamid Abu Zaid, dan Abdullah Saeed - Abdul Aziz; Kusnadi; Aristopan (Indo Publishing, 2025)
This study analyzes the role of Qur'anic hermeneutics (Fazlur Rahman, Nasr Hamid Abu Zayd, Abdullah Saeed) in thematic interpretation to address the contemporary issue of mental health in the digital era. This qualitative research aims to provide a systematic explanation of the obtained facts. The collected data is library-based (Library Research), involving a critical and in-depth study of relevant literature from both primary sources (the Qur'an, exegesis books) and secondary sources (books, journals, articles, websites). The research analyzes verses about tranquility, patience, prayer, and supplication. The results indicate that the universal principles in these verses can be contextualized to build mental resilience against challenges like social comparison, FOMO, and cyberbullying in digital spaces. Using Fazlur Rahman's double movement, it is concluded that internal sources of calm are crucial and that validation should shift from external to internal (God). Through Abu Zayd's humanistic hermeneutics, these verses form a critical-progressive framework for mental health. Abdullah Saeed's contextual approach allows reading them as a value foundation for a healthy relationship with technology, offering a spiritual-psychological framework to build digital resilience, inner validation, and sacred pause. A comparison of the three scholars' hermeneutical applications shows complementary conclusions about building a psychological anchor, critiquing digital culture, and shifting the source of self-worth.